STIMULASI DALAM MEMBANGUN DASAR SAINS DAN MATEMATIKA PADA ANAK USIA DINI - Rosalia Leda; Marli'ah, Siti (Program Studi PG PAUD Universitas PGRI Ronggolawe, 2025)
This article aims to examine the nature of stimulating scientific and mathematical literacy in early childhood, as well as the approaches used to introduce and develop these basic abilities. Based on a literature review of various educational research and theories, this stimulation can be done through various activities involving exploration, observation, experimentation and games that support active learning. Understanding the relationship between this stimulation and children's cognitive development is also discussed, highlighting the long-term benefits that can be achieved, such as increasing problem solving abilities, logic and creativity. In addition, challenges in implementing science and mathematics literacy stimulation in the home and school environment were also identified, including limited resources and uneven understanding among educators. This article concludes that stimulating scientific and mathematical literacy in early childhood is a very important aspect for building a solid knowledge base, which influences children's educational success in the future. Keywords: Early Childhood Education, Scientific Literacy, Mathematics Stimulation